Power and Status in Conflict and Negotiation Research: Introduction to the Special Issue. (11th October 2013) - Greer, Lindred; Bendersky, Corinne
Abstract: Power and status are central influences in conflict and negotiation: Power structures determine negotiator behavior and conflict dynamics, and status differences can give rise to competition and conflicts between individuals and groups. In the last 50 years, much research attention has been devoted to the study of power and status in the conflict setting. In this introduction to the special issue, we highlight some of the key areas of research in the field thus far, highlighting key debates and dialogues. We then present the four articles in this special issue, explaining how each of these articles contributes to a unique debate in this area. Finally, we close with a discussion of the many exciting future research directions that are opening up around the topics of power and status in negotiation and conflict management research.